Epithelial Sodium Channel-α Mediates the Protective Effect of the TNF-Derived TIP Peptide in Pneumolysin-Induced Endothelial Barrier Dysfunction - Czikora, Istvan; Alli, Abdel A.; Sridhar, Supriya; Matthay, Michael A.; Pillich, Helena; Hudel, Martina; Berisha, Besim; Gorshkov, Boris; Romero, Maritza J.; Gonzales, Joyce; Wu, Guangyu; Huo, Yuqing; et al. (Frontiers in Immunology, 2017)
Background Streptococcus pneumoniae is a major etiologic agent of bacterial pneumonia. Autolysis and antibiotic-mediated lysis of pneumococci induce release of the pore-forming toxin, pneumolysin (PLY), their major virulence factor, which is a prominent cause of acute lung injury. PLY inhibits alveolar liquid clearance and severely compromises alveolar–capillary barrier function, leading to permeability edema associated with pneumonia. As a consequence, alveolar flooding occurs, which can precipitate lethal hypoxemia by impairing gas exchange. The α subunit of the epithelial sodium channel (ENaC) is crucial for promoting Na+ reabsorption across Na+-transporting epithelia. However, it is not known if human lung microvascular endothelial cells (HL-MVEC) also express ENaC-α and whether this subunit is involved in the regulation of their barrier function. Methods The presence of α, β, and γ subunits of ENaC and protein phosphorylation status in HL-MVEC were assessed in western blotting. The role of ENaC-α in monolayer resistance of HL-MVEC was examined by depletion of this subunit by specific siRNA and by employing the TNF-derived TIP peptide, a specific activator that directly binds to ENaC-α. Results HL-MVEC express all three subunits of ENaC, as well as acid-sensing ion channel 1a (ASIC1a), which has the capacity to form hybrid non-selective cation channels with ENaC-α. Both TIP peptide, which specifically binds to ENaC-α, and the specific ASIC1a activator MitTx significantly strengthened barrier function in PLY-treated HL-MVEC. ENaC-α depletion significantly increased sensitivity to PLY-induced hyperpermeability and in addition, blunted the protective effect of both the TIP peptide and MitTx, indicating an important role for ENaC-α and for hybrid NSC channels in barrier function of HL-MVEC. TIP peptide blunted PLY-induced phosphorylation of both calmodulin-dependent kinase II (CaMKII) and of its substrate, the actin-binding protein filamin A (FLN-A), requiring the expression of both ENaC-α and ASIC1a. Since non-phosphorylated FLN-A promotes ENaC channel open probability and blunts stress fiber formation, modulation of this activity represents an attractive target for the protective actions of ENaC-α in both barrier function and liquid clearance. Conclusion Our results in cultured endothelial cells demonstrate a previously unrecognized role for ENaC-α in strengthening capillary barrier function that may apply to the human lung. Strategies aiming to activate endothelial NSC channels that contain ENaC-α should be further investigated as a novel approach to improve barrier function in the capillary endothelium during pneumonia.